Opening windows: embracing new perspectives and practices in natural resource social sciences - Sherren, Kate, editor; Thondhlana, Gladman, editor; Jackson-Smith, Douglas, editor; Utah State University Press, publisher; Society and Natural Resource Press, publisher (Colorado State University. Libraries, 2024)
Examines the breadth and relevance of social natural resources knowledge, explores emergent issues and new directions, and captures the increasing diversity of research with disciplinary foundations, approaches, geography, and the divergent interests and backgrounds of scholars.--Provided by publisher.
Introduction: why do we need to open the windows? / Kate Sherren, Douglas Jackson-Smith, Gladman Thondhlana, and Polly Nguyen -- Queer agroecology: exploring nature, agriculture, and sexuality / Jaye Meji?a-Duwan and Michaela Hoffelmeyer -- Gender, land, and agricultural sustainability: working toward greater intersectionality for equity, inclusion, and justice / Angie Carter and Gabrielle Roesch-McNally -- Recent advances in race, ethnicity, and natural resources: research and practice in the United States / John Schelhas, Jasmine K. Brown, Michael Dockry, Sarah Hitchner, Sarah Naiman, and Grace Wang -- Human dignity in natural resource social sciences career pathways / Evan J. Andrews, Christine Knott, Solange Nadeau, Courtenay Parlee, Archi Rastogi, Rachel Kelly, Mari?a Andrée López Gómez, Madu Galappaththi, and Ana Carolina Esteves Dias -- Understanding institutions: the role of broadly institutional perspectives for understanding environmental change and natural resource use / E. Carina H. Keskitalo -- The CBNRM-isation of East and Southern Africa: a critical review of the community conservancy model / Richard Dimba Kiaka, Paul Hebinck, and Rodgers Lubilo -- From authoritative to relational: a typology and analysis of government-community relationships in Nepalese and Australian forest management / Prativa Sapkota, Rebecca M. Ford, Maddison Miller, Andrea Rawluk, and Kathryn J. H. Williams -- Three modes of participatory environmental governance research / John R. Parkins -- Social learning in participatory natural resource management: examining the roles of power and positionality / Christopher Jadallah, Eliza Oldach, and Abraham Miller-Rushing -- Digital tools for participatory environmental decision-making: opportunities, challenges, and future directions / Caitlin Hafferty, Ian Babelon, Robert Berry, Beth Brockett, and James Hoggett -- Image- and arts-based methods in natural resource and environmental social science: scoping the domain for methods that empower / Bryanne Lamoureux, Melanie Zurba, Yan Chen, Durdana Islam, and Kate Sherren -- Understanding environmental concern, values, identity, and other drivers of pro-environmental behavior / Robert Emmet Jones and Tobin N. Walton -- Theorizing the "Anthropos" in the Anthropocene: toward decolonial practices and knowledge co-production / Simon West, Wiebren Johannes Boonstra, and Sasha Quahe -- Re-focusing stewardship on stewards: place-based insights on diversity, relationality, and the politics of land / Jessica Cockburn, Nosiseko Mtati, and Vanessa Masterson -- From roots to rhizomes: place, transitions, and translocality in a less stationary world / Daniel R. Williams and Brett Alan Miller -- Conclusion: what blew in through the windows? / Douglas Jackson-Smith, Gladman Thondhlana, and Kate Sherren.
Keywords: International Association for Society and Natural Resources; Natural resources -- Social aspects; Natural resources -- Management; Agricultural conservation; Environmental policy